Isolation and Screening of Phosphate Solubilizing Bacteria from Rhizosphere of Tea (Camellia Sinensis L.) on Andisols - Fitriatin, Betty Natalie; Widyasmara, Amirah; Arifin, Mahfud; Devnita, Rina; Yuniarti, Anny; Haryanto, Rachmat (International Journal of Sustainable Agricultural Research, 2018)
Andisols is a soil with high retention of phosphate and cannot be absorbed by plants. Some of soil bacteria have the ability to solubilize P and make it available to growing plants are known phosphate solubilizing bacteria (PSB). The research aims to get the kinds of bacteria potential of PSB in the tea plantation. The experiment was conducted at the Laboratory of Biology, Faculty of Agriculture, Padjadjaran University from February 2016 to April 2016. Selection taken from five point blocks with a depth of 0-30 cm and 30-60 cm decision to the topography peaks and slopes. Obtained 23 isolates taken PSB and five isolates with the highest qualitative P solubility test in the soil. The experimental was conducted using Completely Randomized Design, which consists of ten treatments, sterile and non-sterile soil, and five isolates. Incubation was performed for 21 days and the total test bacteria, pH, and P-available every 7, 14, and 21 days. The results showed the best bacterial isolates that capable of solubilize phosphate was taken from A6 block located in the north area of the plantation with a depth of 0-30 cm and is at the peak topography with the ability to dissolve P in the soil is not sterile at 0.997 ppm on the 14th day.